Effect of Preparation Methods on Structure, Redox Properties and CO Oxidation of Ce0.9Pr0.1O2-d Mixed Oxides - Yan, Zong-lan; Shi, Jun (Asian Journal of Chemistry, 2011)
Ce0.9Pr0.1O2-d mixed oxide was prepared by citrate sol-gel, decomposition of nitrate and coprecipitation methods. The effect of preparation methods on catalytic activity for CO has been investigated. The mixed oxide prepared by citrate sol-gel method has the best CO oxidation activity.